“Do You Need a Little Help?”: A Mixed Methods Analysis of 961 Nudges for Blue-Collar and White-Collar Participants During a User Study of Two Digital Information Services - Azem, Jinan Y.; Qadi, Leen F. Al; Rustom, Anas; Salminen, Joni; Jansen, Bernard J. (ACM, 2026)
Usability studies often overlook valuable insights from moderator-to-participant interventions. This study proposes that these interventions, moderator-provided “nudges”, are a rich source of insights on user needs, cognitive load, and system design gaps. We analyzed transcripts from 86 sessions involving two digital library systems and 56 blue-collar (BC) and 30 white-collar (WC) participants, and identified 962 instances of moderator interventions (i.e., nudges). Findings show significant disparities in both the volume and composition of nudges across groups. BC participants required 21 times as many nudges (N=919) as WC participants (N=43). Of the BC participants’ nudges, 737 (80.2%) were system-related, and 182 (19.8%) were user-related. Treating nudges as usability insights for HCI research enables researchers to identify where system scaffolding, such as explicit language, progressive guidance, or simplified workflows, is necessary. The study contributes to inclusive design theory by demonstrating how occupational background influences interventions in user studies and provides design implications for making digital information services more inclusive across occupational groups.
Keywords: Underserved communities; user experience; accessibility; inclusive design; digital inequality; fi=Markkinointi|en=Marketing|